1983
DOI: 10.1016/s0022-5347(17)50956-8
|View full text |Cite
|
Sign up to set email alerts
|

Acetylator Phenotype in Human Bladder Cancer

Abstract: The acetylator phenotype of 26 bladder cancer patients and 26 controls was determined by the sulfamethazine method to evaluate whether patients with the slow acetylator phenotype have a greater susceptibility for bladder cancer. This hypothesis has been suggested by experimental animal and human epidemiological observations. Of the 26 bladder cancer patients 12 (46 per cent) had the slow acetylator phenotype compared to 18 of 26 controls (69 per cent). Within the bladder cancer group there was no striking exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 4 publications
0
12
0
2
Order By: Relevance
“…Some studies of bladder cancer patients have suggested possible associations with the slow acetylator phenotype (Lower et al, 1979;Evans et al, 1983), including tumors related to occupational arylamine exposure (Cartwright et al, 1982), although one study found no relationship with acetylator status (Miller and Cosgriff, 1983). Abnormalities of tryptophan metabolism have long been suspected of playing a role in bladder cancer, and were observed in one high-risk family (Leklem and Brown, 1976), but not in others (Fraumeni and Thomas, 1967;McCullough et al, 1975) or in a population-based survey (Friedlander and Morrison, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of bladder cancer patients have suggested possible associations with the slow acetylator phenotype (Lower et al, 1979;Evans et al, 1983), including tumors related to occupational arylamine exposure (Cartwright et al, 1982), although one study found no relationship with acetylator status (Miller and Cosgriff, 1983). Abnormalities of tryptophan metabolism have long been suspected of playing a role in bladder cancer, and were observed in one high-risk family (Leklem and Brown, 1976), but not in others (Fraumeni and Thomas, 1967;McCullough et al, 1975) or in a population-based survey (Friedlander and Morrison, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…A previous review of 21 published case-control studies reported that experimental evidence was not sufficient to conclude a real increase in risk for urinary bladder cancer in slow NAT2 acetylators (Green et al, 2000). However, subsequent studies carried out in Europe (Vineis et al, 2001), Japan (Tsukino et al, 2004), the United States (Gu et al, 2005) and Spain (Garcia-Closas et al, 2005) each reported that NAT2 slow acetylators had a significantly increased risk of urinary bladder cancer that was stronger in smokers, (Woodhouse et al, 1982;Miller and Cosgriff, 1983;Hanssen et al, 1985;Ladero et al, 1985;Mommsen and Wolf, 1985;Karakaya et al, 1986;Kaisary et al, 1987;Horai et al, 1989;Dewan et al, 1995;Ishizu et al, 1995;Risch et al, 1995;Peluso et al, 1998;Su et al, 1998;Taylor et al, 1998;Hsieh et (Tsukino et al, 2004). Meta-analysis of these and all previous studies show that the overall association with slow NAT2 genotype in the published literature is robust (Figure 7) providing compelling evidence for a role of NAT2 acetylator genotype in urinary bladder cancer associated with aromatic amines in cigarette smoke.…”
Section: Nat2 Polymorphism and Urinary Bladder Cancer Riskmentioning
confidence: 99%
“…In a number of studies of workers, slow acetylation has been reported as a risk factor for bladder cancer. [6][7][8][9][10][11][12] In several of these studies, workers were exposed to arylamine mixtures. 6,13 Other studies did not offer adequate detail of the exposure assessment or analytical methods employed.…”
mentioning
confidence: 99%